Penerapan Metode Waspas dalam Menentukan Pemilihan Peminatan pada Program Studi Teknik Informatika: Array - Lestari, Yuyun Dwi; Perdana, Adidtya (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2020)
Choosing a specialization in a study program is a must for students in semester 4 or 5 and above. This specialization aims to focus students' abilities in one area only. However, many students are wrong in choosing the right subject for them. Most of these students choose specialization based on follow-up without thinking about the impact it will have if the student is unable to take the courses given. For that we need an appropriate technique and calculation so that it is able to help these students in choosing the right specialization. Then a Decision Support System is used which can help in making decisions from the data and criteria used to produce an appropriate decision for students. The method used in this study is the Weight Aggregated Sum Product Assessment method or abbreviated as WASPAS. With the application of the WASPAS method in the selection of specializations, it is hoped that it will be able to provide optimal results, namely the selection of specializations that are in accordance with the abilities possessed by each student.roduce an appropriate decision for students. The method used in this study is the Weight Aggregated.